Heaven's keep [compact disc, unabridged] : a Cork O'Connor mystery - Krueger, William Kent (Krueger, William Kent. Cork O'Connor mystery., 2009)
Every married couple knows you don't go to bed angry. The corollary, Cork O'Connor realizes, is that you also don't say goodbye when you're mad. When the charter plane Jo O'Connor is on crashes over the mountains in Wyoming in an early winter storm, Cork deeply regrets the heated argument he had with his wife just before she left. An intense search is launched, but bad weather and the steep terrain hinder the efforts and soon the search is abandoned.